42 Myocardial Lipid Accumulation and Cardiac Remodelling in Heart Failure with Reduced and Preserved Ejection Fraction. (6th June 2015) - Mahmod, Masliza; Pal, Nikhil; Holloway, Cameron; Ferreira, Vanessa; Dass, Sairia; Francis, Jane; Rider, Oliver; Karamitsos, Theodoros; Ashrafian, Houman; Neubauer, Stefan
Abstract : Introduction: Heart failure (HF) is characterised by alterations in myocardial metabolism with a compensatory shift from fatty acid to glucose metabolism. This could potentially lead to myocardial lipid accumulation (steatosis). We aimed to determine if myocardial lipid is increased in HF with reduced (HFrEF) and preserved (HFpEF) ejection fraction (EF), and assess whether it is related to cardiac structure and function. Methods: 71 subjects (25 HFrEF due to dilated cardiomyopathy-DCM, 18 HFpEF and 28 normal volunteers were prospectively recruited). HFpEF was defined by left ventricular (LV) ejection fraction (EF) >50%, abnormal diastolic function, maximum oxygen consumption < 80% predicted for age, height and gender, with a cardiac limitation in exercise. All subjects underwent cardiovascular magnetic (MR) resonance at 3T for the determination of LV volumes and function and 1 H-MR spectroscopy (MRS) to quantify myocardial lipid/water (%). Results: All subjects were matched for gender, body mass index, blood glucose, free fatty acids and lipid profile. As expected HFrEF patients had significantly increased LV volumes and reduced EF, whilst HFpEF patients had significantly increased LV mass to end-diastolic volume ratio (LV mass/EDV). Importantly, cardiac lipid was increased in both HFrEF and HFpEF when compared to normal controls (cardiac lipid/water 0.67 ± 0.42% in HFrEF; 1.06 ± 0.83% in HFpEF vs. normal controls 0.44 ± 0.17, all p < 0.05), with HFpEF having the highest level of cardiac lipid (Table 1, Figure 1 ). In HFrEF patients, cardiac lipid negatively correlated with LVEF and positively correlated with LV size. In HFpEF, cardiac lipid positively correlated with age and LV mass/EDV. Although HFpEF patients were significantly older, multiple regression analysis showed that age was not an independent predictor of cardiac lipid. Conclusions: Myocardial steatosis occurs in both HFrEF and HFpEF and is related to parameters of LV remodelling. This suggests that myocardial lipid may play a role in the pathophysiological processes of LV remodelling in both HFrEF and HFpEF. Cardiac lipid accumulation may be a potential therapeutic target in these conditions.